2018
DOI: 10.1017/wet.2018.101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Flumioxazin and Metribuzin Postemergence Applications on Soybean

Abstract: All herbicides will move off-target to sensitive crops when not applied correctly. Therefore, low-dose applications of flumioxazin and metribuzin were evaluated in soybean at the unifoliate, V2, and V4 growth stages. Rates evaluated were 12.5%, 25%, and 50% of the labeled use rates of 72 and 316 g ai ha−1 of flumioxazin and metribuzin, respectively. Flumioxazin injury was characterized by necrosis and visible height and width reduction. Injury increased with rate 3 d after treatment (DAT), with unifoliate, V2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Other researchers also reported that higher doses produced more leaf injury when soybean plants were treated with dicamba and metribuzin (McCown et al 2018;Stephenson et al 2018). The influence of genotypes on the injury was also significant because tolerant accessions produce significantly less necrosis than sensitive accessions.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers also reported that higher doses produced more leaf injury when soybean plants were treated with dicamba and metribuzin (McCown et al 2018;Stephenson et al 2018). The influence of genotypes on the injury was also significant because tolerant accessions produce significantly less necrosis than sensitive accessions.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, a reduction in height following the V2 application is what led to greater observed injury. Similarly, Stephenson et al (2019b) reported that metribuzin postemergence at 39.5 and 79 g ai ha −1 , which is 12.5% and 25% of the field use rate, injured V2 soybean greater than unifoliate and V4 soybean at 14, 28, and 42 DAT. Also, fomesafen postemergence at 12.5% of the labeled use rate injured V5 and V7 corn greater than V1, V3, or V9 corn (Sperry et al 2019).…”
Section: Isoxaflutole Studymentioning
confidence: 87%
“…At all locations, treatments were applied with a CO 2 -pressurized backpack sprayer in a constant carrier volume of 140 L ha −1 . Others have simulated off-target movement of herbicides utilizing constant carrier volume (Al-Khatib et al 2003;Bailey and Kapusta 1993;Ellis et al 2003;Sperry et al 2019;Stephenson et al 2019aStephenson et al , 2019bSteppig et al 2018). At Alexandria, all treatments were applied at 190 kPa using four flat-fan 11002 nozzles (AIXR TeeJet®, TeeJet Technologies Southeast, P.O.…”
Section: Concurrentmentioning
confidence: 99%
See 2 more Smart Citations